Multistage-targeted pH-responsive polymer conjugate of Auger electron emitter: optimized design and in vivo activity - Sedlacek, Ondrej; Kucka, Jan; Mattova, Jana; Parizek, Martin; Studenovsky, Martin; Zadinova, Marie; Pouckova, Pavla; Hruby, Martin (European journal of pharmaceutical sciences, 2014)
Auger electrons-emitting radioisotopes (such as iodine-125) are a potentially effective cancer treatment. They are extremely biologically effective, but only within a short range (nanometers). Their use as an effective cancer therapy requires that they will be transported within close proximity of DNA by an intercalator, where they induce double-strand breaks leading to cell death. This type of therapy may be even more beneficial when associated with drug delivery systems. In this report, we describe an optimized triple-targeted polymer delivery system for the intercalator ellipticine, which contains radioisotope iodine-125 with high specific radioactivity (63.2 GBq/mg). This compound is linked to an N-(2-hydroxypropyl)methacrylamide copolymer via an optimized acid-sensitive hydrazone linker. The system is stable at pH 7.4 (representing the pH of blood plasma), and the radioiodine-containing biologically active intercalator is released upon a decrease in pH (44% of the intercalator is released after 24h of incubation in pH 5.0 buffer, which mimics the pH in late endosomes). The active compound is a potent intercalator, as shown with direct titration with a DNA solution, and readily penetrates into cell nuclei, as observed by confocal microscopy. Its polymer conjugate is internalized into endosomes and releases the radioactive intercalator, which accumulates in the cell nuclei. In vivo experiments on mice with 4T1 murine breast cancer resulted in a statistically significant increase in the survival of mice treated with the polymer radioconjugate. The free radiolabeled intercalator was also shown to be effective, but it was less potent than the polymer conjugate.
Keywords: molekulární struktura; Animals; myši inbrední BALB C; Breast Neoplasms; vztahy mezi strukturou a aktivitou; lékové transportní systémy; protinádorové látky; Hydrogen-Ion Concentration; Drug Delivery Systems; nádory prsu; zvířata; elipticiny; Mice, Inbred BALB C; Ellipticines; koncentrace vodíkových iontů; myši; Antineoplastic Agents; Drug Screening Assays, Antitumor; radioizotopy jodu; Female; Polymers; Iodine Radioisotopes; screeningové testy protinádorových léčiv; elektrony; Molecular Structure; polymery; Structure-Activity Relationship; Mice; ženské pohlaví; Electrons